Synthesis, biological evaluation, and in silico studies of new CDK2 inhibitors based on pyrazolo[3,4-d]pyrimidine and pyrazolo[4,3-e][1,2,4]triazolo[1,5-c]pyrimidine scaffold with apoptotic activity - Asmaa A. Mandour; Ibrahim F. Nassar; Mohammed T. Abdel Aal; Mahmoud A. E. Shahin; Wael A. El-Sayed; Maghawry Hegazy; Amr Mohamed Yehia; Ahmed Ismail; Mohamed Hagras; Eslam B. Elkaeed; Hanan M. Refaat; Nasser S. M. Ismail (Journal of Enzyme Inhibition and Medicinal Chemistry)
Cyclin-dependent kinase inhibition is considered a promising target for cancer treatment for its crucial role in cell cycle regulation. Pyrazolo pyrimidine derivatives were well established for their antitumor activity via CDK2 inhibition. In this research, new series of pyrazolopyrimidine derivatives (4–15) was designed and synthesised as novel CDK2 inhibitors. The anti-proliferative activities against MCF-7, HCT-116, and HepG-2 were used to evaluate their anticancer activity as novel CDK2 inhibitors. Most of the compounds showed superior cytotoxic activity against MCF-7 and HCT-116 compared to Sorafenib. Only compounds 8, 14, and 15 showed potent activity against HepG-2. The CDK2/cyclin A2 enzyme inhibitory activity was tested for all synthesised compounds. Compound 15 showed the most significant inhibitory activity with IC50 0.061 ± 0.003 µM. It exerted remarkable alteration in Pre G1 and S phase cell cycle progression and caused apoptosis in HCT cells. In addition, the normal cell line cytotoxicity for compound 15 was assigned revealing low cytotoxic results in normal cells rather than cancer cells. Molecular docking was achieved on the designed compounds and confirmed the two essential hydrogen binding with Leu83 in CDK2 active site. In silico ADMET studies and drug-likeness showed proper pharmacokinetic properties which helped in structure requirements prediction for the observed antitumor activity.